2023
DOI: 10.1159/000528972
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Pathogenic Germline Variants in Women with Non-Familial Unilateral Triple-Negative Breast Cancer

Abstract: Introduction: International guidelines recommend genetic testing for women with familial breast cancer at an expected prevalence of pathogenic germline variants (PVs) of at least 10%. In a study sample of the German Consortium for Hereditary Breast and Ovarian Cancer (GC-HBOC), we have previously shown that women with TNBC diagnosed before the age of 50 years but without a family history of breast or ovarian cancer (sTNBC) meet this criterion. The present study investigates the PV prevalence in BRCA1, BRCA2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Genetic testing for pathogenic variations includes BRCA1/BRCA2 (LoE 1b/A/AGO++), PALB2 (LoE 3a/B/ AGO+), CDH, PTEN, TP53, STK11 (LoE 3b/B/AGO+), and ATM, BARD1, CHEK, RAD51C/D (LoE3a/B/ AGO+/−) with varying degrees of evidence and impact. Genetic testing of BRCA1/2 germline mutations (gBRCA 1/2mut) is strongly recommended to patients, who are candidates for PARPi therapy in early or metastatic disease [11][12][13] or in those under 60 years of age with triple-negative breast cancer, irrespective of familiar or individual history [14]. Mutations in BRCA1/2 and PALB2 are associated with an increased lifetime risk for breast cancer of approximately 40%, for ATM, BARD1, CHEK2, RAD51C, and RAD51D, 20-30%, respectively [15].…”
Section: Breast Cancer Risk Genetics and Preventionmentioning
confidence: 99%
“…Genetic testing for pathogenic variations includes BRCA1/BRCA2 (LoE 1b/A/AGO++), PALB2 (LoE 3a/B/ AGO+), CDH, PTEN, TP53, STK11 (LoE 3b/B/AGO+), and ATM, BARD1, CHEK, RAD51C/D (LoE3a/B/ AGO+/−) with varying degrees of evidence and impact. Genetic testing of BRCA1/2 germline mutations (gBRCA 1/2mut) is strongly recommended to patients, who are candidates for PARPi therapy in early or metastatic disease [11][12][13] or in those under 60 years of age with triple-negative breast cancer, irrespective of familiar or individual history [14]. Mutations in BRCA1/2 and PALB2 are associated with an increased lifetime risk for breast cancer of approximately 40%, for ATM, BARD1, CHEK2, RAD51C, and RAD51D, 20-30%, respectively [15].…”
Section: Breast Cancer Risk Genetics and Preventionmentioning
confidence: 99%
“…In a recent study, data from the GC-HBOC showed elevated prevalence rates in patients with triple-negative breast cancer (TNBC). Therefore, the set of criteria has been extended to include patients with TNBC under the age of 60 without further family history of cancer [14, 15]. Since 2023, as a result of the knowledge-generating healthcare research of the GC-HBOC, a further criterion has been added: as the risk of a pathogenic germline variant in male breast cancer patients is increased compared to the general population, especially for BRCA2 and also for BRCA1 , genetic counseling and analysis should start with one single male breast cancer patient [16, 17].…”
Section: Inclusion Criteriamentioning
confidence: 99%